Integração curricular em uma Escola Agroecológica no sul de Minas: caminhos percorridos pelas educadoras da Educação Infantil e anos iniciais do Ensino Fundamental - Ribeiro, Carollina Martins de Paiva (2021)
In the present work we investigated the development of a process of construction of curricular integration in an Agroecological School of Early Childhood Education and Elementary School (early years), which was located in the rural area of a municipality in the south of the state of Minas Gerais. The study of school curricula is powerful to understand in depth a particular school reality. We start from the understanding of the curriculum as praxis, that is, as a field of communication between theory and practice, understanding it as a document and at the same time as a practice and process by which it seeks to communicate the principles, values and intentions of a given educational proposal closely intertwined with pedagogical practice and school daily life. The curriculum, because it fundamentally is an action of knowledge selection, also has a political dimension, and in it are expressed, explicitly or implicitly, ideas that can contribute both to the maintenance of the status quo, as well as contribute to the overcoming and transformation of it. In the present day, in which neoliberal ideas are increasingly present in our schools, where the "market" and the logic of competition, competitiveness and individualism dictate the rhythm of all spheres of our lives, investigations on initiatives of school communities that seek to build integrated, contextualized, democratic, meaningful curricula that contribute to the integral formation of students, to the construction of critical thinking and to the exercise of enlightened citizenship, have great relevance. For these reasons, we carried out this investigation, understood as a qualitative case study, in which we used as tools for data collection the documentary analysis, especially of the Political-Pedagogical Projects and interviews with semi-structured scripts carried out with the group of teachers and with the director, representative of the school's management team. From the data analysis, we verified that the process of construction of curricular integration in the studied school context was based on Interior Ecology, that is, on the search for an integral education and for the formation of values, coming from the Buddhist Philosophy of S. Ema. Chagdud Tulku Rinpoche, and agroecology, which represented the link between Buddhist Philosophy and the physical (natural/rural) and social environment in which the School was inserted, permeating the integrative activities and projects and inspiring the construction of the meanings of curricular integration. For the realization of curricular integration in school daily life and educational practices, it was of paramount importance to strengthen collaborative work and the union of the school team. This strengthening was mainly constructed through the creation of daily collective times intended both for the planning of integrative activities and projects and for moments of personal and professional reflection, interiorization and artistic activities. Thus, we affirm that, based on the experience investigated, the integration of a pedagogical work presupposes the integration of people.